Anti-inflammatory and anticancer activities of (-)-zeylenol from stems of Uvaria grandiflora - Phikunkeaw Seangphakdeea (2018)
Uvaria grandiflora has stimulated rigorous phytochemical investigation aimed at determining chemical structures and biological activities. In recent years, many polyoxygenated cyclohexenes have been isolated from this genus. This study reports that zeylenol isolated from the stems of U. grandiflora possess potential anti-inflammatory, anticancer, and caspase-3 activities. The structure of this compound was elucidated from spectroscopic analysis, particularly 2D NMR techniques. The anti-inflammatory effect and toxicity of zeylenol were evaluated in animal models and compared to that of reference drugs. In addition, the cytotoxicity of the isolated compound against human breast cancer MDA-MB231 and hepatocellular carcinoma HepG2 cell lines were studied. The test (-)-zeylenol at the dose of 1 mg/ear significantly inhibited oedema formation by 90%, 69%, 52%, and 52% after 15, 30, 60, and 120 min, respectively. Zeylenol was found to be toxic to both MDA-MB231 and HepG2 cells in a dose response manner with IC 50 values of 54±10 and > 80 μM, respectively. The compound induced MDA-MB231 cell apoptosis via caspase-3 activation. Zeylenol probably possesses anti-inflammatory activity by inhibiting the synthesis or release of various inflammatory mediators and might be used to induce human breast cancer MDA-MB231 cell apoptosis.